INVESTIGATING THE FACTORS THAT INFLUENCE BREAST SELFEXAMINATION PRACTICES AMONG FEMALE UNDERGRADUATES IN RIVERS STATE - Adiele, Ijeoma Obinna (International Journal of Contemporary Health Sciences and Technology, 2024)
This study investigated the factors influencing breast self-examination among female undergraduates in public tertiary educational institutions in Rivers State, Nigeria. A descriptive research design was adopted for this study with a population consisting of forty-four thousand, eight hundred and sixty-four (44,864) female university undergraduates in Rivers State. A sample size of 1,200 was selected using a multi-stage sampling procedure. The instrument for data collection was a structured questionnaire with a reliability coefficient of 0.74. Data collected were analysed using point biserial correlation at 0.05 level of significance. The finding of the study showed that statistically significant relationship was found between practice of breast self-examination and variables such knowledge [f(1,1172) = 4925, p<0.05], age [f(1,1172) = 8248.73, p<0.05] and religious affiliation [f(1,1172) = 3946.40, p<0.05]. It was concluded that the factors influencing breast self-examination among female undergraduates in public tertiary educational institutions in Rivers State, Nigeria were knowledge of cervical cancer, age and religious affiliation of the female undergraduates. It was recommended among others, that nongovernment health organizations should create awareness about BSE by carrying out monthly awareness campaign in the different tertiary educational institutions